Synthesis of potentially biologically active aromatic and hetero-aromatic compounds - Reynolds, Chevonne (My University, 2011)
The first part of this dissertation deals with employing the use of multi-component coupling reactions (MCC) for the synthesis of large diverse compound libraries. A review of selected literature identified the growing need for more potent and selective HIV/AIDS drugs due to the extremely high mutation rate of the HI virus. We thus chose to test our synthesised compound library against the HIV enzyme, reverse transcriptase (RT) in the hopes of identifying a potential novel non-nucleoside reverse transcriptase inhibitor (NNRTI). Two different MCC approaches were used in order to give two different classes of compounds; firstly the Groebke-Blackburn reaction for the synthesis of imidazo[1,2-a]pyridines and secondly a reaction developed by Poigny and co-workers for the synthesis of 3-amino-1-cyano-indolizines. We were successful in utilizing the Groebke-Blackburn to synthesise a variety of imidazo[1,2-a]pyridines in varying yields. However, all of the compounds showed poor inhibition of the RT enzyme in the biological assay. We thus turned our attention to the synthesis of the 3-amino-1-cyano-indolizines, which proved to be very difficult. It was discovered that this reaction did not proceed to completion and the product generally isolated from this MCC reaction was the more stable aldol condensation intermediate. In some of the experiments we were able to isolate mostly small quantities of indolizine compound, but when tested against the RT enzyme the results once again were very poor. A short review in the second section of this dissertation showed the lack of methodology available for the synthesis of the dihydrobenzo[b]phenanthridine motif which constitutes the backbone of a secondary metabolite known as Jadomycin B. The major aim of this segment of the project was thus to develop methodology to synthesise this biologically important scaffold. However, our methodology failed to yield the desired product as it was not possible to reduce the nitrile intermediate to the required amine. In an attempt to determine whether similar methodology could be used for the synthesis of pyranonaphthoquinone containing compounds an unexpected and novel reaction was discovered. It was found that treatment of [2-(1,4-dimethoxynaphthalen-2-yl)phenyl]methanol with brominating agent NBS results in the synthesis of a naphthopyranone ring system known as 12-methoxy-6H-dibenzo[c,h]chromen-6-one. Following this discovery it was attempted to elucidate the mechanism by which NBS performs this novel reaction. Unfortunately we were unable to determine the exact mechanism responsible for this transformation conclusively. The most likely mechanism shows NBS oxidising the benzylic alcohol to an aldehyde, which is then converted to an acid bromide facilitating ring closure. Finally we wished to determine if this strategy could be applied in the synthesis of related naphthopyranone ring systems, which was shown to be possible with the synthesis of 3-bromo-2-methoxy-6H-benzo[c]chromen-6-one.